ECHO Care: Providing Multidisciplinary Specialty Expertise to Support the Care of Complex Patients - Komaromy, Miriam (J Gen Intern Med, 2019)
BACKGROUND: Programs for high-need, high-cost (HNHC) patients can improve care and reduce costs. However, it may be challenging to implement these programs in rural and underserved areas, in part due to limited access to specialty consultation. AIM: Evaluate the feasibility of using the Extension for Community Health Outcomes (ECHO) model to provide specialist input to outpatient intensivist teams (OITs) dedicated to caring for HNHC patients. SETTING: Weekly group videoconferencing sessions that connect multidisciplinary specialists with OITs. PARTICIPANTS: Six OITs across New Mexico, typically consisting of a nurse practitioner or physician assistant, a registered nurse, a counselor or social worker, and at least one community health worker. PROGRAM DESCRIPTION: OITs and specialists participated in weekly teleECHO sessions focused on providing the OITs with case-based mentoring and support. PROGRAM EVALUATION: OITs and specialists discussed 427 highly complex patient cases, many of which had social or behavioral health components to address. In 70% of presented cases, the teams changed their care plan for the patient, and 87% reported that they applied what they learned in hearing case presentations to other HNHC patients. DISCUSSION: Pairing the ECHO model with intensive outpatient care is a feasible strategy to support OITs to provide high-quality care for HNHC patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05205-1) contains supplementary material, which is available to authorized users.